2014
DOI: 10.1016/j.tranon.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Binding Protein 7 Is a Molecular Marker in Adenoid Cystic Carcinoma of the Salivary Glands: Implications for Clinical Significance

Abstract: Adenoid cystic carcinoma (ACC) is an aggressive malignant neoplasm of the salivary glands. Its diagnosis is difficult due to overlapping features with other salivary tumors. Gene expression analysis may complement traditional diagnostic methods. We searched gene expression patterns in the Gene Expression Omnibus (GEO) database and in our tumor and normal samples. The biologic and prognostic potential of the identified genes was analyzed. The GEO data set of primary xenografted ACCs revealed that expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Ten retrospective studies including 658 patients with ACC fulfilled the inclusion criteria and were included in this meta‐analysis (Figure ) . Three studies without outcome events were excluded, and one study that investigated the impact of MYB mRNA on prognosis was also excluded . The characteristics of the 10 eligible studies are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten retrospective studies including 658 patients with ACC fulfilled the inclusion criteria and were included in this meta‐analysis (Figure ) . Three studies without outcome events were excluded, and one study that investigated the impact of MYB mRNA on prognosis was also excluded . The characteristics of the 10 eligible studies are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Roden et al employed a break‐apart FISH probe strategy, whereas West et al used a come‐together and break‐apart FISH probe strategy, with two probes flanking the MYB gene and one probe located at the 3′ end of the NFIB gene. Furthermore, some studies detected MYB‐NFIB fusion products by reverse‐transcriptase polymerase chain reaction, in which the primer design, positive cutoff, and multiplexing factors influenced assay outcomes . Brill et al found MYB‐NFIB fusion in 86% of ACCs using fresh frozen tissues, in contrast to 44% when using formalin‐fixed paraffin‐embedded tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, FABP7 is a shared NOTCH1/SOX10 target that marks neural stem cells in the subventricular CNS zone, as well as CSC in glioblastoma . Fatty acid‐binding protein 7 is coexpressed with SOX10 in ACC and basal‐like breast cancers, and in these tumor types FABP7 expression serves as a diagnostic marker associated with poor prognosis . Although the mechanism of FABP7 activity in cancer or CSC maintenance is not well described, activation of FABP7 in cancers increases fatty acid uptake resulting in enhanced cell survival and protection against reactive oxygen species …”
Section: Resultsmentioning
confidence: 99%
“…An important insight into this cooperation, which has not been previously appreciated, was provided by the co-expression of FABP7 that relied on both NOTCH1 and SOX10, and the role of FABP7 in regulating expression of genes critical for cell survival. FABP7 has been recently described as a novel diagnostic and prognostic ACC marker (48) and was also implicated in glioblastoma, melanoma, and basal-like breast cancer; however, its downstream targets and molecular mechanisms of activation have not been studied. Our data associate FABP7 with the expression of SKP2 and multiple other genes involved in survival, proliferation, and metabolic pathways pointing at a novel signaling pathway that stimulates CSC in ACC.…”
Section: Discussionmentioning
confidence: 99%